Incentivized mergers and cost effciency: Evidence from the electricity distribution industry - Robert Clark; Mario Samano (Queen's University, Department of Economics, 2020)
In an effort to lower costs of provision, authorities have encouraged the consolidation of providers for a number of services such as electricity distributors, school boards, hospitals, and municipalities. In this paper we propose an endogenous merger process to evaluate the impact of government-provided incentives on consolidation patterns, and to evaluate the resulting outcomes. The process takes as input estimates from a stochastic frontier cost model, which yields an average cost curve for the industry. Policy parameters are used to simulate final configurations using offers that are the output of a Nash Bargaining problem. The efficiency of candidate merged entities is determined by a relative-influence function that measures the degree to which the combination of the involved firms' levels of efficiency results in cost-increasing amalgamations, and an interconnection cost that measures the impact of the size of the conglomerate that is formed. We calibrate parameters by applying the merger process to replicate the observed industry reconfiguration and then use these parameters to simulate the consolidation patterns that would have resulted from different policy incentives. We apply the method to the case of Ontario, where past mergers of local electricity distribution companies were incentivized by transfer tax reductions and a further round of mergers was recently proposed. Our findings suggest that the proposed tax incentive would have no impact on efficiency levels and consolidation patterns, and that even a substantial subsidy would still leave about five times as many LDCs as desired by policy makers.
Keywords: 330